Kajian Yuridis Terhadap Tanggung Jawab Notaris Dalam Pembuatan Surat Kuasa Membebankan Hak Tanggungan - Udiyana, Ida Ayu Agung Nara Kirana; Sarjana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 03 (2021)DO - 10.24843/AC.2021.v06.i03.p15, 2021)
Abstract The purpose of this article is to find out a juridical study in making SKMHT according to the Mortgage Law and the responsibilities of a Notary in making SKMHT according to the applicable rules. The method on this article is used normative legal research with  statutory approach, a conceptual approach, and a case approach. The results of the discussion, namely the SKMHT study of the UUHT contained in Article 15 paragraph (1) of the UUHT explains: "The Power of Attorney to impose Mortgage must be made with a notary deed or PPAT deed". In this regulation, a Notary/PPAT have an authority to make SKMHT on that form of a deed, but in fact it fills in fields/blanks/forms that have been prepared by the land agency. The formulation of legal norms in Article 15 paragraph (1) UUHT contains contradictions. In one side , the regulation requires the encumbrance of Mortgage to be made or stated in a Notary deed, but on the other si d e, it requires the power to encumber Mortgage to be made with a notarial deed/PPAT deed in the form of a “Letter”. So that , SKMHT does not qualify as an authentic deed. Also, the Notary's responsibilities in the form of authority in carrying out his/her duties are stated in Article 15 of the UUJN, so that the authority can provide legal certainty that can be accounted for by the Notary which consists of 3 important aspects, namely: Outward Aspects; Formal Aspects and Material Aspects.   Abstrak Tujuan penulisan artike l ini untuk mengetahui kajian yuridis dalam p embuatan SKMHT menurut UU Hak Tanggungan serta mengena i tanggung jawab Notaris dalam pembuatan SKMHT menurut aturan yang diberlakukan. Metode riset yang dipakai ialah jenis pen e litian hukum normatif dengan pendekatan peraturan perundangan, pendekatan konseptual, pendekatan kasus. Adapun hasil pembahasan yai t u mengenai kajian SKMHT dari UUHT yang terdapat pada Pasal 15 ayat (1) UUHT menjelaskan: “Surat Kuasa Membebankan Hak Tanggungan wajib dibuat dengan akta notaris atau akta PPAT”. Dalam peraturan tersebut, Notaris/PPAT mempunyai kewenangan dalam membuat SKMHT dalam bentuk akta, namun dalam praktiknya mengisi isian/blangko/formulir yang telah disiapkan oleh instansi pertanahan. Rumusan norma hukum dalam pasal 15 ayat (1) UUHT mengandung pertentangan. Dalam satu sisi peraturan tersebut mewajibkan membebankan Hak Tanggungan yang dibuat atau dituangkan dengan akta Notaris, namun disisi lain mensyaratkan kuasa membebankan Hak Tanggungan dibuat dengan akta notaris/akta PPAT dalam bentuk “Surat”. Sehingga, SKMHT tidak memenuhi syarat sebagai akta otentik. Serta, pertanggung jawaban Notaris berupa kewenangan dalam menjalankan tugas jabatannya tercantum dalam Pasal 15 UUJN, sehingga dalam kewenangan tersebut dapat memberikan kepastian hukum yang dapat dipertanggungjawabkan oleh Notaris yang terdiri dari 3 aspek penting yaitu: Aspek Lahiriah; Aspek Formal dan Aspek materiil.